IMPLEMENTASI METODE WARD UNTUK PENGELOMPOKAN KECAMATAN BERDASARKAN DATA UNMET NEED KB PADA IBU HAMIL DI KABUPATEN SLEMAN DIY TAHUN 2021 - Zikriandhini Zikriandhini; Kariyam Kariyam (UPT Penerbitan Universitas Jember, 2022)
Family planning is one of the government's efforts to control the population rate in Indonesia. The family planning program in Indonesia has been proven nationally and internationally to reduce fertility rates for couples of childbearing age. However, the government's policy in controlling the population rate still faces several obstacles in its implementation, one of which is the high number of unmet needs without family planning participation. The unmet need for family planning can be used as the main focus in activating the family planning program to control the population rate. This study provides an overview and maps of sub-districts in Sleman, Special Region of Yogyakarta based on the number of unmet needs in pregnant women using descriptive statistics and hierarchical clustering methods, namely the ward method. The results showed that there were two groups of sub-districts with cluster 1 (high intensity) amounting to 8 sub-districts and cluster 2 (low intensity) totaling 9 sub-districts. Keywords: Descriptive Statistics, Hierarchical Clustering, Unmet Need, Ward Method